Borders that continue to bother us: the politics of cross-border security cooperation in Africa's Lake Chad Basin. Issue 4 (2nd October 2017) - Agbiboa, Daniel E.
ABSTRACT: Until 2014, security responses to the Boko Haram insurgency were largely domestic and military. However, the increasing expansion of Boko Haram attacks in the Lake Chad Basin (LCB), compounded by the consequent humanitarian crisis, compelled a joint security action. This came in the form of the rejuvenated Multinational Joint Task Force (MNJTF), comprising forces from the LCB member states (Nigeria, Cameroon, Niger, and Chad) and Benin. My goal in this paper is to interrogate the cross-border dynamics and ramifications of the Boko Haram insurgency, and the nature of security responses to it. The analysis extends to the politics of cross-border security cooperation against Boko Haram in the LCB, as well as the impact of the MNJTF on Boko Haram's evolving tactics. Along the way, the paper identifies key challenges to the effective operationalisation of the MNJTF.